Artikel Review : Metode Analisis Pewarna Metanil Yellow Pada Makanan Dan Minuman - Ahmad, Dzakiyyah Sulthanah; Hanifa, Nisa Isneni (Universitas Muhammadiyah Klaten, 2025)
Colorants are one of the food additives that serve to provide or enhance the color of food, thereby increasing the visual appeal of the product. Metanil yellow is an illegal azo dye used in food that can cause health effects such as toxic methemoglobinemia, cyanosis, anemia, and may trigger tumor formation. Based on this issue, this article aims to summarize qualitative and quantitative analysis techniques for metanil yellow, including their advantages and limitations, as a reference for food safety monitoring. The method employed is a literature review of both national and international indexed articles, with inclusion criteria for scientific articles related to the analysis of metanil yellow in food and beverages published in the last 10 years (2015–2025). Based on the literature review conducted, qualitative testing can be performed using Test Kits, Thin Layer Chromatography, UV-Vis Spectrophotometry, and FT-IR Spectroscopy, while quantitative analysis can be conducted using UV-Vis Spectrophotometry and High-Performance Liquid Chromatography (HPLC).